Non‐invasive tests for fibrosis and liver stiffness predict 5‐year survival of patients chronically infected with hepatitis B virus. Issue 10 (5th April 2013) - de, V.; Vergniol, J.; Barthe, C.; Foucher, J.; Chermak, F.; Le, B.; Merrouche, W.; Bernard, P.‐H.
Summary Background Liver stiffness and non‐invasive tests predict overall survival in chronic hepatitis C. However, in patients chronically infected with hepatitis B virus (HBV), only the association between liver stiffness and the risk of hepatocellular carcinoma has been published. Aim To evaluate the 5‐year prognostic value of liver stiffness, non‐invasive tests of liver fibrosis, and liver biopsy, to predict overall survival in chronic hepatitis B. Methods In a consecutive cohort, we prospectively assessed fibrosis, with liver stiffness, FibroTest, APRI, FIB‐4 and liver biopsy (if indicated). We examined death and liver transplantation during a 5‐year follow‐up, and factors associated with overall survival. Results A total of 600 patients (men 64%, mean age 42 years, inactive carriers 36%) with chronic hepatitis B were included. At 5 years, 25 patients were dead (13 liver‐related deaths) and four patients had liver transplantation. Overall survival was 94.1% and survival without liver‐related death 96.3%. No liver‐related death was observed in inactive carriers. Survival was significantly decreased in patients diagnosed with severe fibrosis, whatever the non‐invasive method used (P < 0.0001), or liver biopsy (P = 0.02). Patients' prognosis decreased as liver stiffness and FibroTest increased. In multivariate analysis, FibroTest and liver stiffness had the highest hazard ratio with survival. The association persisted after adjustment on age, necro‐inflammatory histological activity presumed by ActiTest and treatment. Conclusions Liver stiffness measurement or FibroTest can predict survival in chronic HBV infection. Thus, these tools may help physicians to early assess prognosis and discuss specific treatments, such as liver transplantation.